Analysis of Determinan of Stunting Prevalence among Stunted Toddlers in Indonesia - Agus Joko Pitoyo; Agustinur Saputri; Riska Eka Agustina; Tri Handayani (Populasi)
Stunting is regarded as one of the nutritional problems in Indonesia. The prevalence of stunted toddlers in Indonesia showed a decline from 37.2 percent in 2013 to 30.8 percent in 2018. However, this was still far from the WHO target, which should be less than 20 percent. There were two objectives of this study, firstly, to determine the general condition of health and nutrition of toddlers as well as the general condition of households in Indonesia. The second one was to examine the determinants of stunting in toddlers. The data were obtained from Riskesdas 2018, Podes 2018, and population projections per district/city from Statistics Indonesia. The method was carried out using descriptive and inferential analysis. The findings showed that all regions in Indonesia, excluding DKI Jakarta, experienced cases of stunted toddlers categorized in high and very high categories. The regression results confirmed that the prevalence of malnutrition toddlers, the prevalence of obese toddlers, complete basic immunization coverage, the prevalence of chronic energy deficiency in women of childbearing age, the proportion of villages that had adequate midwives per population, as well as the coverage of access and clean water sources had a significant effect on the prevalence of stunted toddlers in Indonesia. The case of stunted toddlers was mainly caused by poverty, bad lifestyle, inadequate health services, and low access to clean water. Therefore, the government policies are then needed, especially those related to socio-economic determinants.